Analysis of the Characteristics of Carbon Prepreg Sandwich Composites with Polyurethane Foam as Core Material in the Body of the Malem Diwa Proto Vehicle - Alsudais, Alsudais (Yayasan Kawanad, 2024)
A sandwich composite, formed by the macroscopic integration of two or more materials with distinct properties, exhibits unique mechanical characteristics. This study investigates the influence of carbon prepreg layer thickness and polyurethane foam core thickness on the mechanical properties of sandwich composites through tensile and flexural testing. Tensile tests followed ASTM D3039 standards, while flexural tests adhered to ASTM C393. Composites were fabricated with either two or four layers of carbon prepreg using an autoclave process. The two-layer composite specimens measured 250 mm in length, 25 mm in width, and 0.5 mm in thickness, whereas the four-layer specimens had a thickness of 1 mm. Flexural test specimens had dimensions of 250 mm in length, 75 mm in width, a 10 mm core thickness, and a 2 mm skin thickness. The two-layer composite achieved a maximum tensile stress of 645.1 MPa, a Young’s modulus of 39.89 GPa, and an elongation of 2.08%. The four-layer composite reached a maximum tensile stress of 955.05 MPa, a Young’s modulus of 34.93 GPa, and an elongation of 1.82%. The average flexural strength of the polyurethane foam core sandwich composite was 10.6 MPa. These results indicate that layer thickness significantly affects tensile properties, while the core material influences flexural performance.